Contextual impairments in Schizophrenia and the FN400 - Amoruso, Lucía (2012)
Our brains are good at extracting and proccessing social contextual cues. Ongoing information is rapidly linked to memory traces of previous experiences, allowing us to generate predictions which help us interpret daily situations. These predictions are a core aspect of human cognition as long as they make social behaviors more effcient. Current evidence, however, suggests that schizophrenia patients are less able to benefit from context and, consequently, social impairments are commonly observed in this complex disorder.